None Shall Look Back - Gordon, Caroline (J.S. Sanders, 1992)
A study of the hero in his archetypal struggle against death, this novel follows the Civil War in the West through the career of Confederate Rivers Allard, a Kentuckian who rides with Forrest. Southern Classics Series.